ACARICIDAL ACTIVITY OF COMBINED COMMERCIAL STRAINS OF ENTOMOPATHOGENIC FUNGI AGAINST Amblyomma mixtum AND Rhipicephalus microplus TICKS - Dora Romero Salas; Jose Luis Bravo Ramos; Daniel Sokani Sánchez Montes; Carolina Cárdenas Amaya; Jannete Gamboa Prieto; Anabel Cruz Romero; Angelica Olivares Muñoz (Tropical and Subtropical Agroecosystems, 2022)
Background: Rhipicephalus microplus and Amblyomma mixtum are the most important tick species affecting livestock in tropical areas. They can have a direct harmful effect on cattle and humans due to transmission of pathogens of tick-borne diseases (TBD). Entomopathogenic fungi have an important role in crop pest control. However, data concerning the efficacy of use of entomopathogenic fungicombinations are scarce. Objective: For this reason, in this study, the efficacy of commercial fungal combinations was assessed: Trishok® (Trichoderma harzianaum and Trichoderma virens) and Esporomax® (Beauveria bassiana, Metarhizium anisopliae, Paecelomyces fumosoroseus). Methodology: Adult immersion tests were performed with six different concentrations of fungal solutions. Results: In this study, Trishok® and Esporomax® showed potential efficacy against R. microplus. Different concentrations of fungal application tested on A. mixtum did not show any effect. The observed mortality of R. microplus was 85. 0 ± 2.0 and 65.0 ± 2.0 for Trishok® and Esporomax®, respectively. The estimated LC50 for R. microplus immersed in solutions of Trishok® and Esporomax® thereof were: 6.5x104 and3.9x105 conidia mL-1, respectively. Implications: These results should be considered in the design and implementation of alternatives based on the biological control of ticks. Conclusion: We can conclude that combined commercial strains of entomopathogenic fungi have in vitro acaricidal activity against R. microplus.